Exploring circularity in the electric vehicle (EV) sector - Ong, Kai Zheng (Nanyang Technological University, 2024)
The burgeoning electric vehicle (EV) industry, despite addressing the climate concerns, also faces challenges related to resource utilization and an increase in EV waste. To tackle these issues, this study reviews the circularity framework within the EV sector, which promotes better resource utilization through reuse and upcycling - a vital strategy for sustainability. Furthermore, various countries have enacted recycling and research & development policies to provide legal and policy support for advancing recycling technology. This report will explore and compare different recycling technologies. Additionally, it includes an analysis with key players in the EV industry to pinpoint the gaps in the EV materials chain and strategies to reduce waste. Interviews with diverse EV stakeholders will offer insights into the innovative approaches companies are adopting to address these challenges. By adopting circular economy principles, the EV sector can serve as a blueprint for a sustainable future, reducing its environmental impact and promoting a resource-efficient economy.